An Inquiry into Iranian Religious Eulogists’ Mental Models; a Qualitative Analysis with Strategic Approach - Mostafa jafari (Religion & Communication, 2021)
The objective of this survey is extracting and analyzing the mental models of Iranian religious eulogists with a strategic approach. Mental models shape people’s perceptions– eulogists in this research- of the function of a system. Mental model has three components: mental images, imaginations and assumptions.This survey is a qualitative one using grounded theory. The target community members are the 17 eulogists in north- west provinces of Iran. The saturation technique has determined the number of interviews.  The data have been collected via structured interviews. They have been analyzed by three qualitative data analysis techniques: continuous comparison, typology and semi statistic.The analysis of 700 data propositions have lead to sixteen results and extraction of eleven mental models. These findings did show that the mental images and imaginations of eulogists about five components of their task are positive and about three components are negative. Theirs assumptions are not testable. They feel proud about the history of eulogy but are anxious about its future. They have no practical solutions for this matter. In short, the mental models of eulogists are: simple, precise, transparent, superficial, relatively static, closed (limited), biased, unscientific, interreligious and inter-vocational. A transformation in mental models is needed to enhance the strategic function of this community.